A TRANSPOSIÇÃO DIDÁTICA DE TÓPICOS DE NANOCIÊNCIAS RELACIONADOS COM HIDROFOBICIDADE PARA O ENSINO MÉDIO - Pistoia, Rafael Piovesan (2016)
This thesis aimed to develop and implement a didactic module for high school, punctuating the view of modern physics and interdisciplinary concepts of Nanoscience via didactic transposition. The survey was conducted for 49 students of the second year of high school of the Instituto Estadual de Educação Mãe de Deus located in Tupanciretã in Rio Grande do Sul. The focus is mean and motivate students in their learning and scientism, whose educational material originates the educational product - didactic module that will be displayed in virtual learning space “Mais UNIFRA”. This module makes up content that establish hydrophobicity issue, surface tension, among others, worked together with Physics in their approaches "classic / modern." The nine classes were developed in the renderings of meaningful learning, seeing seek evidence of learning and anchor them in their mental processes of knowledge. The material was organized to meet the teaching methodology of the Three Pedagogic Moments, considering the reality of the student in teaching situations and experiences, contributing to the organization of knowledge and research. The activities present in the educational product may be support for teaching and research in the high school teachers and students, enabling them to improve their knowledge of the Science, Technology and Society. It is that will bring out the importance of knowledge and didactic transposition to the efficiency of the construction of knowledge from the educator's skills, from what is produced in the academy for school spaces, especially in the teaching and learning Physics. Verification of new nanoscience knowledge via hydrophobicity occurred through a production and comparison of conceptual maps. The analysis tool was efficient for the strategy developed by promoting interaction and giving rise to the interest of students in physics. The participation and responsibility also reflected in the know-how of the mentor-teacher himself, as it was evident in the positive results of the work committed to disseminate and promote attitudes and methodologies front of other colleagues from other areas of knowledge.